2018
DOI: 10.1021/acsnano.8b02805
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Rugged Nanoscaffold To Enhance Plug-and-Display Vaccination

Abstract: Nanoscale organization is crucial to stimulating an immune response. Using self-assembling proteins as multimerization platforms provides a safe and immunogenic system to vaccinate against otherwise weakly immunogenic antigens. Such multimerization platforms are generally based on icosahedral viruses and have led to vaccines given to millions of people. It is unclear whether synthetic protein nanoassemblies would show similar potency. Here we take the computationally designed porous dodecahedral i301 60-mer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
252
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(256 citation statements)
references
References 86 publications
4
252
0
Order By: Relevance
“…Recently, methods that enable coupling of complex antigens to pre-formed VLP have been developed, employing the SpyTag/SpyCatcher conjugation system [31,33,34]. Employed in mice, these VLP vaccines have induced high and stable IgG levels against microbial antigens, including malaria antigens [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methods that enable coupling of complex antigens to pre-formed VLP have been developed, employing the SpyTag/SpyCatcher conjugation system [31,33,34]. Employed in mice, these VLP vaccines have induced high and stable IgG levels against microbial antigens, including malaria antigens [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous covalent isopeptide bond forms between a lysine residue of the SpyCatcher domain (13 kDa) and an aspartic acid of its pairing peptide SpyTag (13 amino acid residues) in a sitespecific manner, without the need of additional reagents nor enzymes at broad ligation conditions (Reddington and Howarth, 2015). The advantageous properties of the SpyTag/SpyCatcher chemistry makes it an excellent protein ligation tool for surface functionalization of various organic and inorganic materials, such as virus-like particles (Brune et al, 2016(Brune et al, , 2017Bruun et al, 2018), protein-based scaffolds (Bae et al, 2018;Choi et al, 2018;Swartz and Chen, 2018;Zhang et al, 2018a), gold nanoparticles (Ma et al, 2018), silica (Zhang et al, 2018b,c), quantum dots (Ke et al, 2018;Brizendine et al, 2019), and crystalline graphene (Tyagi et al, 2018). We recently developed a modular PHA platform using SpyTag/SpyCatcher chemistry, where we successfully showed that purified SpyTagged proteins could ligate to SpyCatcher-coated PHA spheres in vitro with decent tunability (Wong and Rehm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that those conjugates exhibited a range of different functions (Bae et al, ; Choi et al, ; Moon et al, ). The ST/SC protein ligation system has been applied for displaying various antigenic proteins and targeting ligands on VLPs and their effective immune response inductions and cell‐specific gene delivery were successfully demonstrated (Brune et al, , ; Bruun, Andersson, Draper, & Howarth, ; Janitzek et al, ; Kasa, Raneni, Chamoun‐Emanuelli, Wright, & Chen, ; Ke et al, ; Leneghan et al, ; Singh et al, ; Thrane et al, ).…”
Section: Introductionmentioning
confidence: 99%